THE DEVELOPMENT OF BOOK TO PUPPET VIDEO MEDIA FOR ENGLISH LEARNING IN PAUD SURYA GEMILANG MALANG - Wardani, Agista; Warnanda, Kharisma Naidi; Wiraatmaja, Triastama (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The community service aims to develop the book has been made by the team in the previous community service. The book consists of two short stories in English that is used for learning and teaching English in PAUD Surya Gemilang, Malang. The book was made because books in the school are mostly expensive. The way how the team develop the book is to change it to puppet video. At the end, the video would be attached to the book by putting QR code on the book. Thus, the English learning in PAUD Surya Gemilang, Malang, will be richer and more pleasant, the teacher would be easier to teach and the students would enjoy learning English